Analisis Kesesuaian Prinsip Ta’awun dan Tabarru Dengan Sistem Pengelolaan Risiko Sharing Of Risk Dalam Asuransi Syari’ah - Naila Alya Fadila Hilman; Falha Himatul Aliyah; Mutiara Ramadhani; Joni (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
Abstract The development of Islamic financial institutions is growing rapidly in line with the increasing public demand for financial protection systems that are in accordance with Islamic principles. One such form is Islamic insurance, which serves as an alternative to conventional insurance, which is often considered to contain elements of gharar (uncertainty), riba (usury), and maisir (speculation). This paper aims to examine the concept of risk sharing in Islamic insurance and compare it with the concept of risk transfer in conventional insurance. The research method used is a qualitative approach through library research by analyzing relevant literature, scientific journals, and regulations. The results of the study show that the concept of risk sharing in Islamic insurance is based on the principles of ta'awun (mutual assistance) and tabarru' (voluntary donation), in which participants collectively help each other in facing risks. This concept creates a system that is more fair, transparent, and socially just, as well as strengthening the values of solidarity and trust among participants. Meanwhile, the transfer of risk system in conventional insurance tends to cause contractual imbalances and potentially violates sharia principles. Thus, risk sharing can be viewed as a risk management model that is not only in line with Islamic values but also strengthens the social and economic sustainability of Islamic insurance participants. Keywords: Sharia Insurance, Sharing of Risk, Tabarru, Ta’awun, Transfer of Risk Abstrak Perkembangan lembaga keuangan syariah semakin pesat seiring dengan meningkatnya kebutuhan masyarakat terhadap sistem perlindungan finansial yang sesuai dengan prinsip Islam. Salah satu bentuknya adalah asuransi syariah, yang hadir sebagai alternatif dari asuransi konvensional yang sering dianggap mengandung unsur gharar (ketidakpastian), riba, dan maisir (spekulasi). Tulisan ini bertujuan untuk mengkaji konsep sharing of risk (berbagi risiko) dalam asuransi syariah serta membandingkannya dengan konsep transfer of risk pada asuransi konvensional. Metode penelitian yang digunakan adalah pendekatan kualitatif melalui studi kepustakaan (library research) dengan menganalisis literatur, jurnal ilmiah, serta peraturan yang relevan. Hasil kajian menunjukkan bahwa konsep sharing of risk dalam asuransi syariah berlandaskan pada prinsip ta’awun (tolong-menolong) dan akad tabarru’ (hibah sukarela), di mana peserta secara kolektif saling membantu dalam menghadapi risiko. Konsep ini menciptakan sistem yang lebih adil, transparan, dan berkeadilan sosial, serta memperkuat nilai solidaritas dan kepercayaan antar peserta. Sementara itu, sistem transfer of risk pada asuransi konvensional cenderung menimbulkan ketidakseimbangan akad dan berpotensi melanggar prinsip syariah. Dengan demikian, sharing of risk dapat dipandang sebagai model pengelolaan risiko yang tidak hanya sesuai dengan nilai-nilai Islam, tetapi juga memperkuat keberlanjutan sosial dan ekonomi peserta asuransi syariah. Kata kunci: Asuransi Syariah, Sharing of Risk, Tabarru, Ta’awun, Transfer of Risk